(untitled) - Jernigan, Leigh Ann; Boggess, Damon; Holmes, Kena; Dye, Luke; Willis, Curt; Freeman, Cheryl A.; Engine 15 Media Group; Willrock Entertainment; Mill Creek Entertainment (Mill Creek Entertainment, 2015)
The Freeman Family, Jack, Judy and their young daughter Charlie, has always opened their home to rescued animals, and when the house became too small they opened a zoo with the help of Mr. Baker, their dependable zoo keeper. Known as The Little Ponderosa Zoo, it has been a huge hit for their small town, but a banker and towns mayor think the property is on top of a gold mine and devise a plan to get the gold for themselves.
Keywords: Zoos; Juvenile films; Zoo keepers; Juvenile films; Families; Juvenile films; Childrens films; Feature films